Peer Review - thriving or ailing in the twenty-first century? (Midlands Medicine, 2007)
The use of independent peer reviewers, to obtain advice from experts knowledgeable in a particular research area, is an intrinsic and essential part of the allocation of funds and the publication of results. For around 150 years, the vast majority of researchers have put their faith, and their future career, in an anonymous peer review process which is a fundamental underpinning of high quality world science and, ultimately, of evidence-based medicine. But is peer review in good health, or fit-for-purpose in the twenty-first century? Of course like any process or convention, scientists often question the process of peer review, usually when they have just received a rejection of their latest grant proposal or carefully crafted paper! But an observer of British and American science in the last five years might be forgiven for thinking that, in the internet age, peer review as we know it has reached a difficult period of ill-health, even perhaps its declining years. To use another metaphor, peer review appears increasingly under attack as dated, blunt and unsophisticated tool in the service to the scientific community. This short article aims to summarise where we are now, after about a year of quite intensive scrutiny of scientific peer review to try to diagnose its problems and offer a prognosis for its future.